Effect of Processing and Heat Treatment on the Phase Kinetics, Microstructure, and Hardness Behavior of CoCrFeMnNi High Entropy Alloy - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Rao, K. Raja; Lee, Hansung; Song, Eunhyo; Ahn, Byungmin (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2025)
In this study, an equiatomic CoCrFeMnNi high entropy alloy (HEA) was prepared by powder metallurgy (PM) and casting methods. Both processed HEAs exhibited face-centered cubic (FCC) and Cr-rich sigma (σ) phases. To mitigate the presence of undesirable Cr-rich σ phase, heat treatment was performed at 800 °C, 1000 °C, and 1200 °C for 5 hours. The effects of heat treatment (HT) temperature on phase, microstructure, and hardness properties of HEAs were investigated. The PM-processed HEA exhibited superior microhardness (~408 ± 10 HV), nanohardness (~6.54 GPa), and elastic modulus (~254.29 GPa) compared to the as-cast HEA due to its fine-grained and uniform microstructure. However, increasing heat treatment temperatures caused a reduction in hardness and elastic modulus in both processed HEAs, due to grain coarsening and reduced fraction of the Cr-rich σ phase. The present study highlights the critical role of heat treatment in optimizing the phase, microstructure, and hardness behavior of HEAs produced by PM and casting techniques.
Keywords: As-cast; Casting method; Effect of heat treatments; Face-centred cubic; Face-centred-cubics; Heat treatment temperature; High entropy alloys; Phase kinetics; Property; Sigma (σ) phase